2007
DOI: 10.1016/j.bone.2006.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia affects mesenchymal stromal cell osteogenic differentiation and angiogenic factor expression

Abstract: Mesenchymal stromal cells (MSCs) seeded onto biocompatible scaffolds have been proposed for repairing bone defects. When transplanted in vivo, MSCs (expanded in vitro in 21% O(2)) undergo temporary oxygen deprivation due to the lack of pre-existing blood vessels within these scaffolds. In the present study, the effects of temporary (48 h) exposure to hypoxia ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
208
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(225 citation statements)
references
References 56 publications
(30 reference statements)
15
208
1
1
Order By: Relevance
“…Furthermore, perfusion culture of MSCs stimulates the synthesis of growth factors including bone morphogenetic protein-2 (BMP-2), FGF-2, TGF-b1, and vascular endothelial growth factor (VEGF) [100]. Hypoxia also enhances MSC expression and secretion of VEGF [101]. The Michaelis-Menten constitutive equations for oxygen consumption assume the rate constant is independent of time and material, and cell density primarily influences the oxygen profile [102].…”
Section: D Expansionmentioning
confidence: 99%
“…Furthermore, perfusion culture of MSCs stimulates the synthesis of growth factors including bone morphogenetic protein-2 (BMP-2), FGF-2, TGF-b1, and vascular endothelial growth factor (VEGF) [100]. Hypoxia also enhances MSC expression and secretion of VEGF [101]. The Michaelis-Menten constitutive equations for oxygen consumption assume the rate constant is independent of time and material, and cell density primarily influences the oxygen profile [102].…”
Section: D Expansionmentioning
confidence: 99%
“…13,14 Even though MSCs are located very closely to vascular structures, they are often still found in a relatively low oxygen environment, which further supports the finding that a hypoxic surrounding may be necessary in order to maintain the cells' undifferentiated state. 7 Hypoxia leads to decreased adipogenic and osteogenic differentiation, 15,16 triggering the release of angiogenic factors as well as promoting the expression of vasculogenic characteristics and functions in MSCs. 17,18 With physiological conditions in mind, there are proliferation benefits for cells cultured in low oxygen environments.…”
Section: Hypoxiamentioning
confidence: 99%
“…The expression of HIF-1α was decreased with the time of hypoxia, whereas the expression of core binding factor alpha 1 (Cbfα1), another key transcription regulator involved in the chondrocyte differentiation and ossification, was increased gradually (Rabie et al 2004;Augello and De Bari 2010). However, other report showed that temporary exposure to hypoxia would inhibit the expression of Cbfα-1/Runx2 in MSCs (Potier et al 2007).…”
mentioning
confidence: 93%